The effect of novel fin shapes and non-uniform magnetic field on the nanoparticles embedded PCM melting in a tube - Farahani, Somayeh Davoodabadi; Farahani, Amir Davoodabadi; Tayebzadeh, Fatemeh; Öztop, Hakan Fehmi (Elsevier, 2022)
In this paper, the heat transfer and melting process of the phase change material (PCM) in a cylindrical space with different internal fins with the presence of nanoparticles and a non-uniform magnetic field (NUMF) are inspected numerically. Seven new fin models have been designed for this purpose. The enthalpy-porosity method based on FVM is used to simulate the melting process of PCM in a 3D state. Lauric acid as PCM and Ferric nanoparticles were utilized. The electric field is created using the electric potential. Their outcomes demonstrate that the process of PCM melting in the finned chamber is a strong function of geometric shape. Among the designed fins, Type 6 geometry has the most improvement in the melting process. The new fins are designed to improve the melting process by about 2-40%. The nanoparticles volume fraction (NPVF) is 2.55%. The conse-quences display that with increasing NPVF from 2.5 to 5%, the melting fraction has increased by about 1.5-2.5%. Applying NUMF on the outer walls of the chamber has amended. This effect is proportional to the intensity of the magnetic field. With increasing the intensity of the magnetic field by about 16-57%, an improvement in the melting process has been observed.
Keywords: Phase change material; Melting; Novel fin; Non-uniform magnetic field; Nanoparticles